ANALISIS PENGARUH UPAH MINIMUM PROVINSI DAN INFLASI TERHADAP PENGANGGURAN TERBUKA DI SULAWESI TENGGARA - Mulyadi Mulyadi; Wali Aya Rumbia; Wa Ode Rachmasari Ariani (Universitas Halu Oleo, 2022)
This research aims to recognize the influence of provincial minimum wage (UMP) and inflation on open unemployment both simultaneously and partial.The analytical tool used is multiple linear regression analysis. The result show that simultaneously provincial minimum wage (UMP) and inflation significantly influence on open unemployment in Southeast Sulawesi Province period year 2004-2020. Partially, provincial minimum wage (UMP) have a negative and significant influence on the open unemployment, while inflation did not significantly affect the open unemployment in Southeast Sulawesi Province.